A Fiqh Reconstruction in Company Zakat Accounting - Irfan Irfan; Muhyarsyah Muhyarsyah (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
The paper aims to explore the concept of the company from the aspects of Islamic law (fiqh) and sharia, as the basis in determining the company as muzakki, thus raising the legal obligation for companies to pay zakat through the zakat accounting calculation method. This study is designed to reconstruct the concepts of fiqh and sharia in muamalah (economic) activities within the framework of aqidah, sharia and akhlak through ijtihad. The research uses qualitative analysis, through a literature study approach by exploring various classical and contemporary sources. This paper found that the company is synonymous as syirkah on the basis of syakhshiyyah i’tibariyyah (spiritual entity) or syakhshiyyah hukmiyyah, referred to as al-dhimmah, that is, inherent traits of humans, as expert al-form (the right to receive) and syahhshiyyah al-ada (the right to fulfill responsibilities). So, the company as the subject of zakat has an obligation to pay zakat based on five principles inherent in the company as muzakki. The calculations are carried out by using the company zakat accounting method based on established standards (AAOIFI), (MASB), and (IAI). The determination of companies as subjects of zakat, which has the obligation to pay zakat, certainly has positive implications for the realization of a fair and equitable distribution of wealth, as well as the emergence of corporate social responsibility (collectively) and the responsibility of a Muslim (individually) in realizing his worship. to Allah SWT, an increase in community welfare can be achieved.